Решите уравнение: а) (x−5)(x+5)=2(x−3)^2−x^2 б) (2x+3)^2−4(x−1)(x+1)=64 в) 3(x+5)^2−4x^2=(3−x)(3+x) г) (3x+1)^2−(3x−2)(2+3x)=19 д) 6x^2−(3x−3)(2x+1)=0 е) (x+1)(x+2)−(x+4)(x+5)=0 ё) 42x^2−(6x−3)(7x−1)=105 ж) (x−2)(x−7)−(x+2)(x−10)=0

Zadornov200215 Zadornov200215    1   21.07.2019 12:30    0

Ответы
Okean111 Okean111  31.07.2020 17:28
Начну с решения:
a) x^2-25=2x^2-12x+18-x^2
    12x=43
    x= 3 целых 7/12
б) 4x^2+12x+9-4x^2+4=64
     12x=51
     x=4,25
в) 3x^2+30x+75-4x^2=9-x^2
     30x= -66
     x= -3,3
г) 9x^2+6x+1-6x-9x^2+4+6x=19
    6x=14
    x= 2 целых 1/3
д) 6x^2-6x^2-3x+6x+3=0
     3x= -3
     x= -1
е) x^2+2x+x+2-x^2-5x-4x-20=0
    -6x=18
     x=-3
ё) 42x^2-42x^2+6x+21x-3=105
     27x=108
     x=4
ж) x^2-7x-2x+14-x^2+10x-2x+20=0
    -x=-34
     x=34
    
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра